PERANCANGAN ALAT UJI STATIS PROPELLER THRUST GAUGE UNTUK UAV LISTRIK SKALA KECIL: Indonesia - Suwandito, Yoan Ario (J-ENSITEC, 2023)
Static testing of the propeller is necessary to take into account the amount of thrust generated by the propeller before it is attached to the propulsion system. However, for small-scale static testing, especially on the Unmanned Aerial Vehicle (UAV) propulsion system, it is still difficult to find. So the purpose of this research is to design and manufacture a static test tool for propeller thrust combined with a DC brushless motor, especially in the Unmanned Aerial Vehicle (UAV) propulsion system. This test tool uses the Arduino Uno Atmega 328 as its microcontroller which is directly integrated with the load cell sensor which functions as the main measuring tool for the amount of thrust generated by the propeller rotation. In the load cell, there is a change in voltage in the strain gauge resulting in a change in resistance, then the results of the change will be read by the HX711 module. The HX711 module will convert the analog signal generated by the load cell into a digital signal, making it easier for Arduino to read data. Measurement results in data from Arduino will be displayed via the 16x2 LCD. This research proposes a simple propeller thrust gauge static test that can measure forces from 0 N to 49 N with an error rate of 0.479%.